ORODISPERSIBLE TABLET: A Patient Friendly Dosage Form (a Review) - K., Rameesa C.; K., Drisya M. (BALI MEDICAL JOURNAL; Vol 4 No 1 (2015), 2015)
Background: The most common and preferred route of drug administration is through the oral route. Orodispersible tablets are gaining importance among novel oral drug delivery system as they have improved patient compliance and have some additional advantages compared to other formulation. They are also solid unit dosage forms, which disintegrate in the mouth within a minute in the presence of saliva due to superdisintegrants in the formulation. Thus this type of drug delivery helps a proper per oral administration in pediatric and geriatric population where swallowing is a matter of trouble. Various scientists have prepared orodispersible tablets by following various methods. However, the most common method is the direct compression method. Other special methods are Freeze Drying,Tablet Molding, Sublimation, Spray Drying, Mass extrusion, Phase transition process, etc. Since these tablets dissolve directly in the mouth, so, their taste is also an important factor. Various approaches have been taken in order to mask the bitter taste of the drug. A number of scientists have explored several drugs in this field. Like all other solid dosage forms, they are also evaluated in the field of hardness, friability, wetting time, moisture uptake, disintegration test and dissolution test.
Keywords: Disintegration; Manufacturing process; Orodispersible tablets; Superdisintegrants.